Time, change and reality - Pickup, MJ (2012)
In my thesis I will be proposing situationalism: a new theory of how it is that things change over time. It is B-theoretic, eternalist and endurantist. The central contention of the theory is that what is true can differ in a metaphysically significant way from time to time. The theory emerges as a solution to the problem of change. In my first chapter, I argue that change is genuinely problematic (contra some of the recent literature). There are at least three ways to generate problems from change, and I elucidate problems from the law of non-contradiction and the indiscernibility of identicals. In the second chapter, I examine the nature of change and contend that the current major solutions to the problem fail to uphold our intuitive notion of change. Chapter 3 introduces the idea of a situation; a part of reality. The fourth chapter applies situations to the problem of change and comes up with a new solution. The solution relies on a denial of universal persistence; the denial of the idea that what is true in a situation s is thereby true in every situation of which s is a part. Chapter 5 considers the infamous Ship of Theseus case, and concludes that situationalism can also solve this problem. The situationalist account of the Ship of Theseus puzzle enables us, in Chapter 6, to briefly demonstrate the analogous application of the solution to a series of other persistence puzzles. The seventh chapter discusses the metaphysical consequences of such a view. The core claim is of the primacy of parts of reality over reality as a whole. It is a position according to which truth in situations is fundamental and situations needn’t cohere. I hold that the theory has significant costs but also substantial benefits. For this reason it is worth serious consideration.